Navigating Organized Urology A Practical Guide - Nakada, Stephen Y.; Patel, Sutchin R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This extensively revised second edition of the text discusses the management of various aspects of the professional life of newly qualified urologists as well as more experienced urologists. It features clear, easy-to-read chapters covering various topics, including clinical and surgical patient care, administrative duties, and research in today's hectic practice environment. New topics covered include how to manage an operating theater, telemedicine and how to manage crisis situations. Lessons acquired from the authors experiences of the COVID-19 Pandemic are also detailed. Navigating Organized Urology: A Practical Guide systematically presents a range of practical strategies for a successful transition from trainee to practicing urologist, while also offering more experienced urologists a fresh perspective on efficient management and successful adaptation of their practices for the modern age.
Knowing Yourself -- Self-Awareness -- Priorities -- Relationship Management -- For the Graduating Resident or Fellow -- Interview Skills -- Curriculum Vitae Preparation -- Finding the Right Job -- Negotiating Your First Contract -- Seeking the Best Environment -- Academic Roles -- Educator -- Teaching on Rounds -- Teaching in the Operating Room -- How to Constructively Criticize Residents -- Administrator -- Researcher -- Writing a Paper -- Finding Funding -- Presentation skills -- Finding Your Niche -- Grant Writing -- Inventor -- Collaborator -- Clinical and Day to Day Aspects of Work -- Patient Satisfaction -- Managing the Operating Room -- Office Management -- Billing and Coding -- Telemedicine -- Time Management -- Press and Social Media -- Burnout and Work-Life Balance -- The Power of History and Leveraging Past Institutional Success -- Crisis Management for Physicians -- Practical Lessons Learned From the Covid-19 Pandemic -- Re-evaluating Yourself. .
Keywords: Urology; Surgery; Public health administration; Urology; Surgery; Health Administration; Urology; Practice Management, Medical; Career Choice; Professional Autonomy